2022
DOI: 10.1038/s41598-022-05782-y
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous controls and microRNA profile in female patients with obstructive sleep apnea

Abstract: Recent studies have evaluated the potential of circulating microRNAs (miRNAs) as valuable biomarkers for characterizing obstructive sleep apnea (OSA) in males. The potential use of miRNAs as clinical indicators in females is unknown. The objective is to identify a set of miRNAs to be used as endogenous controls (ECs) in female patients with OSA. Then, to analyze differences in the miRNA expression profile between patients with and without OSA. This observational, longitudinal study included 85 females with sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…These findings are consistent with those of Kelch et al (2017) and Meder et al (2014). Zapater et al (2022) addressed gender differences for miRNAs in the OSA-targeted population, but their work investigated mi-croRNA molecules different from ours. It should also be noted that there is still a lack of research on this topic.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings are consistent with those of Kelch et al (2017) and Meder et al (2014). Zapater et al (2022) addressed gender differences for miRNAs in the OSA-targeted population, but their work investigated mi-croRNA molecules different from ours. It should also be noted that there is still a lack of research on this topic.…”
Section: Discussionsupporting
confidence: 88%
“…Recent scientific literature has papers dealing with the potential of microRNAs in the field of OSA. Zapater et al (2022) published a paper highlighting the high potential of micro RNAs in this regard. Sánchez-de-la-Torre et al (2015, co-authors of other publications agree that it is now possible to identify specific microRNAs associated with OSA and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, due to the sex-disparity in miRNA expression patterns [37], the same methodology was performed in females. A set of three miRNAs (miR-30a-5p, miR-93-3p and miR-532-5p) was identified as the most stable to be used as endogenous controls in the determination of circulating miRNAs in OSA [38]. Subsequently, Santamaria-Martos et al [39] identified a profile of six miRNAs that contributes significantly to the diagnosis of the disease.…”
Section: Micrornas In Obstructive Sleep Apnoeamentioning
confidence: 99%